A mobilidade urbana no Brasil: Percepç\~oes de sua populaç\~ao - Ernesto Pereira Galindo; Vicente Correia Lima Neto (Instituto de Pesquisa Econômica Aplicada (IPEA), 2019)
– This work presents the results of a research on urban mobility of the Social Perception Indicator System held in 2011, by the Ipea. In this document it is discussed the current mobility context in Brazil and, throughout the text, made a characterization of the population by the most used transport mode. It is also considered in the analysis the population's perception of the city and the public transportation used by them. The people's perception related to the travel time in the various modes of transport and the difficulties pointed to the realization of that travel are also taken into account in the study. Lastly, we propose an analysis of the mobility's problems from the general perception of its users.
Keywords: R28; R40; O18; 330; urban mobility; social perception